SAFETY OF LONGTERM THERAPY WITH WARFARIN: POSSIBILITY OF TREATMENT RENEWING AFTER HEMORRHAGIC COMPLICATIONS - E. S. Kropacheva (Столичная издательская компания, 2016)
The safety of anticoagulant therapy is discussed. Warfarin position in prevention of thrombotic complications is analyzed according to the evidence base medicine approach. Possible hemorrhagic complications of warfarin are described and accompanied with clinical cases. Possibility of renewal of anticoagulant therapy in patients after hemorrhagic complications is discussed.